2015
DOI: 10.1016/j.joen.2015.09.005
|View full text |Cite
|
Sign up to set email alerts
|

Apical Transportation, Centering Ability, and Cleaning Effectiveness of Reciprocating Single-file System Associated with Different Glide Path Techniques

Abstract: The different glide path techniques promoted minimal apical transportation, and the reciprocating single-file system tested remained relatively centralized within the root canal. Also, the different techniques interfered in the cleaning effectiveness of the reciprocating system.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
73
1
2

Year Published

2016
2016
2019
2019

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 47 publications
(79 citation statements)
references
References 25 publications
(35 reference statements)
3
73
1
2
Order By: Relevance
“…Creating a glide path can prevent these mishaps (de Carvalho et al . ). Several recent studies showed that the use of NiTi pathfinding rotary files are more effective than hand files in achieving a glide path with minimal mishaps (Berutti et al .…”
Section: Discussionmentioning
confidence: 97%
“…Creating a glide path can prevent these mishaps (de Carvalho et al . ). Several recent studies showed that the use of NiTi pathfinding rotary files are more effective than hand files in achieving a glide path with minimal mishaps (Berutti et al .…”
Section: Discussionmentioning
confidence: 97%
“…Simulated artificial canals are different in terms of microhardness when compared to root dentin, and the effects created by heat generation during instrumentation can affect the instruments’ cutting blades [36]. Ever since CBCT was introduced in dentistry, it has been widely recognized as an accurate, noninvasive tool that allows quantitative and qualitative three-dimensional evaluation of root canals [30, 32, 37]. In the present study, CBCT image technology was used to evaluate canal transportation and centering ability following root canal preparation with different rotary and reciprocating instruments.…”
Section: Discussionmentioning
confidence: 99%
“…Studies conducted on curved root canals of extracted teeth also yielded similar results. [2132] Although the difference was not statistically significant, de Carvalho et al . [21] reported better centering ability when PathFile instruments were used before another single reciprocating NiTi instrument (25/.08) compared with that in the absence of glide path creation.…”
Section: Discussionmentioning
confidence: 98%
“…[2132] Although the difference was not statistically significant, de Carvalho et al . [21] reported better centering ability when PathFile instruments were used before another single reciprocating NiTi instrument (25/.08) compared with that in the absence of glide path creation. They stated that the values observed in the no glide path group indicate a decreased ability of the reciprocating instrument to adhere to the central axis of the root canal, thus demonstrating the instrument's tendency to not follow the original canal path when a glide path is not created.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation